A critical interrogation of paradigms in discourse on the decolonisation of higher education in Africa - Hungwe, J. P.; Ndofirepi, A. P. (South African Journal of Higher Education, 2021)
There have been persistent contestations over the conceptual implications of paradigms in the decolonisation of higher education in Africa. As a contribution towards the continued pursuit of a succinct conceptualisation of decolonisation, this conceptual article interrogates four paradigms that undergird the decolonisation of higher education in Africa. These paradigms – decolonisation as Africanisation, decolonisation as indigeneity in education, racial undertones, and decolonisation as Ubuntu – are employed as benchmarks for decolonisation. The unexamined entrenchment of these paradigms within the decolonisation of higher education, however, tends to encumber the intended goals of that process. The conclusion arrived at here, is that while decolonisation is a noble cause that must be pursued consistently; the distortion of these paradigms ultimately hinders the objectives of decolonizing African higher education.